IMPLEMENTASI KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN KINERJA GURU RAUDATUL ATFAL - Varelasiwi, Retno Shiama; Maisyaroh, Maisyaroh; Burhanuddin, Burhanuddin (Universitas Islam Negeri Alauddin Makassar, 2023)
The purpose of this research was to find out the implementation of transformational leadership styles in improving teacher performance at the Kindergarten/RA level. The principal as a leader has a lot of influence on the sustainability of the quality of education in schools and educational institutions. Teachers as educational actors who communicate directly with education consumers are expected to be able to show good and optimal performance in providing services. The method used in this research is qualitative by collecting data through several techniques such as interviews, documentation and field observation. Then the data obtained is reduced according to the focus of research, analyzed and conclusions drawn. Based on the results of the study, it showed that the transformational leadership carried out by the head of the RA AL-Mahmud Bacem school was able to increase teacher motivation and performance in optimizing their competence.